2006
DOI: 10.1038/sj.onc.1209966
|View full text |Cite
|
Sign up to set email alerts
|

Matriptase inhibition by hepatocyte growth factor activator inhibitor-1 is essential for placental development

Abstract: Hepatocyte growth factor activator inhibitor-1 (HAI-1) is a Kunitz-type transmembrane serine protease inhibitor that forms inhibitor complexes with several trypsin-like serine proteases and is required for mouse placental development and embryo survival. Here we show that the essential function of HAI-1 in placentation and all other embryonic processes is to restrict the activity of the type II transmembrane serine protease, matriptase. Enzymatic gene trapping of matriptase combined with HAI-1 immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
142
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(152 citation statements)
references
References 26 publications
9
142
0
1
Order By: Relevance
“…Our results are consistent with findings in other transmembrane serine proteases. Oberst et al (23) have shown that an N-glycosylation site in the protease domain is critical for the activation of matriptase, a type II transmembrane serine protease essential for the development of multiple epithelial tissues (37)(38)(39). Similarly, Zheng et al (24,25) have shown that N-glycans in the enteropeptidase protease domain are important for the apical targeting of this digestive enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with findings in other transmembrane serine proteases. Oberst et al (23) have shown that an N-glycosylation site in the protease domain is critical for the activation of matriptase, a type II transmembrane serine protease essential for the development of multiple epithelial tissues (37)(38)(39). Similarly, Zheng et al (24,25) have shown that N-glycans in the enteropeptidase protease domain are important for the apical targeting of this digestive enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…Background buffer subtraction and conversion of the data to absolute scale by use of water as a primary standard was performed using the SUPERSAXS program package. 3 The instrumental sample-to-detector distance was set to 640 cm, giving a q range of 0.01-0.345 Å Ϫ1 , where q is the length of the scattering vector, defined as q ϭ 4sin()/, where is the x-ray wavelength at 1.54 Å and 2 is the scattering angle between the incident and scattered beam. The final intensity is I(q), in units of cm Ϫ1 .…”
Section: Saxs Data Collection and Analysismentioning
confidence: 99%
“…The deletion of the 60-loop (chymotrypsin template numbering) was accomplished by substitution of DDRGFR (Asp 660 -Arg 665 ) with GG using site-directed mutagenesis. To introduce the StrepII tag in the C terminus of the matriptase catalytic domain, the StrepII tag (SAWSHPQFEK) was fused to the C terminus with an additional (GS) 3 linker.…”
Section: Recombinant Protein Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, mice lacking HAI-1/SPINT1 have completely impaired placental labyrinth layer development, and the concomitant deletion of the matriptase/St14 gene rescues this phenotype. 6,7 In mouse skin, HAI-1/SPINT1 interacts with matriptase to play a central role in regulated keratinization of the epidermis. 8,9 The participation of HAI-1/SPINT1 in the maintenance of epidermal integrity in zebrafish was also demonstrated.…”
mentioning
confidence: 99%